LDL Receptor and Pcsk9 Transcripts are Decreased in Liver of Ovariectomized Rats: Effects of Exercise Training - Ngo Sock, E. T.; Chapados, N. A.; Lavoie, J.-M. (Hormone and Metabolic Research, 2014)
The aim of this study was to determine the effects of ovariectomy in rats on hepatic gene expression of key molecules involved in cholesterol metabolism and to verify if exercise training may play a role in preventing hypercholesterolemia in Ovx rats. Sprague-Dawley rats were ovariectomized (Ovx) or sham-operated (Sham) and were either trained (Tr) on treadmill or kept sedentary (Sed) for 8 weeks. Rats were divided into 5 groups: Sham-Sed, Sham-Tr, Ovx-Sed, Ovx-Tr and Ovx with 17β-estradiol supplementation (Ovx-E2). Ovx animals had significantly (p<0.05) higher body weight, adiposity, liver total cholesterol (TC) content and hypercholesterolemia compared to Sham rats. In contrast, gene expression of hepatic low-density lipoprotein receptor (LDL-R), LDL receptor-related protein (Lrp1), proprotein convertase subtilisin/kexin type 9 (Pcsk9), sterol regulatory element binding protein 2 (SREBP-2) and 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCoA-r) were reduced (p<0.05) in Ovx compared to Sham rats. Hepatic mRNA levels of scavenger receptor class B member 1 (SR-B1) and ATP-binding cassette subfamily A member 1 (ABCA1) (hepatic and intestinal) were higher (p<0.05) in Ovx compared to Sham rats. All of these molecular changes were corrected in Ovx-E2. Exercise training, significantly reversed the effect of Ovx on adiposity, plasma triglyceride, TC and mRNA expression of SREBP-2 but had no effect on all other hepatic genes expression. These data indicate that hypercholesterolemia in Ovx rats is associated with a reduction of hepatic LDL-R and Lrp1 gene expression.
Keywords: hypercholesterolemia; ABCA1; SR-B1; hepatic cholesterol; Lrp1